Ionic charge transport in strongly structured molten salts - Tatlipinar, H; Amoruso, M; Tosi, MP (ELSEVIER SCIENCE BV, 2000)
Data on the DC ionic conductivity for strongly structured molten halides of divalent and trivalent metals near freezing are interpreted as mainly reflecting charge transport by the halogen ions. On this assumption the Nernst-Einstein relation allows an estimate of the translational diffusion coefficient D-tr of the halogen, in at least one case (molten ZnCl2) D-tr is much smaller than the measured diffusion coefficient, pointing to substantial diffusion via neutral units, The values of D-tr estimated from the Nernst-Einstein relation are analyzed on the basis of a model involving two parameters, i.e. a bond-stretching frequency w and an average waiting time tau. With the help of Raman scattering data for w, the values of are evaluated and found to mostly lie in the range 0.02-0.3 ps for a vast class of materials. (C) 2000 Elsevier Science B.V. All rights reserved.
Keywords: ionic transport; self-diffusion in liquids; molten salts; NEUTRON-DIFFRACTION; SELF-DIFFUSION; CHLORIDE; MELTS; TRICHLORIDE; Physics